2013
DOI: 10.1111/jgh.12112
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between toll‐like receptor‐4 signaling and angiotensin‐II in liver fibrosis development in the rat model of non‐alcoholic steatohepatitis

Abstract: These studies indicated that the cross talk between TLR4 signaling cascade and AT-II plays a pivotal role in liver fibrosis development in non-alcoholic steatohepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 42 publications
3
38
0
1
Order By: Relevance
“…However, AT-II could not stimulate the signaling pathways downstream of TLR4 without LPS because TLR4 is not the downstream receptor of AT-II. LPS with AT-II significantly promoted LPS-induced activation and ARB significantly blocked AT-II mediated TLR4-LPS signaling cascade, leading to significant reduction in TGF-b1 production in Ac-HSC [14]. These findings reinforce the notion that cross talk between AT-II and TLR4 signaling plays a substantial role in the liver fibrosis development by regulating TGF-b1 production in Ac-HSCs.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, AT-II could not stimulate the signaling pathways downstream of TLR4 without LPS because TLR4 is not the downstream receptor of AT-II. LPS with AT-II significantly promoted LPS-induced activation and ARB significantly blocked AT-II mediated TLR4-LPS signaling cascade, leading to significant reduction in TGF-b1 production in Ac-HSC [14]. These findings reinforce the notion that cross talk between AT-II and TLR4 signaling plays a substantial role in the liver fibrosis development by regulating TGF-b1 production in Ac-HSCs.…”
Section: Discussionsupporting
confidence: 79%
“…The inhibitory effects of ARB mostly coincided with the suppression of activated hepatic stellate cells (Ac-HSC) [13]. Moreover, we demonstrated AT-II augmented LPS-TLR4 signaling through AT1R and ARB improved hepatic fibrogenesis and reduced TLR4-mediated innate immune signaling in Ac-HSC [14]. These results indicate that combined UDCA and ARB may have utility in the treatment of NASH.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Second, Ekihiro S, et al isolated primary quiescent HSCs followed by magnetic antibody cell sorting with antibody against F4/80 antigen and CD11b-conjugated microbeads to remove Kupffer cells and macrophages. This procedure may activate primary quiescent HSCs and up-regulate TLR4 expression, because primary quiescent HSCs are easily to be activated even by culturing for certain time in dish [36]. Therefore, an efficient crosstalk must need up-regulation of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Shirai et al [36] reported that Ang II could up-regulate TLR4 mRNA expression in activated rat HSCs by culturing on plastic plates for 7 days. This is consistent with our observations both on rat HSC cell line and primary HSCs, in which TLR4 protein levels were assessed by western blotting in vitro and immunofluorescence in vivo .…”
Section: Discussionmentioning
confidence: 99%